Theoretical and applied research on bistable dual-piezoelectric-cantilever vibration energy harvesting toward realistic ambience. (18th October 2016) - Gao, Y; Leng, Y; Javey, A; Tan, D; Liu, J; Fan, S; Lai, Z
Abstract: Pink noise, which is similar to realistic ambient noise, is normally used to simulate ambience where a piezoelectric energy harvesting system (PEHS) is set up. However, pink noise with standard spectral representation can only be used to simulate excitations assumed to possess constant intensity, whereas realistic ambient noise normally appears with a random spectrum and varying intensity in terms of different locations and time. The output performance of conventional bistable magnetic repulsive energy harvesters is significantly affected by the ambience intensity. Considering this fact, a model bistable dual-piezoelectric-cantilever energy harvester (DPEH) is developed in this study to achieve optimal broadband energy harvesting under a varying-intensity realistic circumstance. We utilized various realistic ambient conditions as excitations to obtain the DPEH energy harvesting performance for theoretical and applied study. The elastically supported PEHS has been proven to be more adaptive to realistic ambience with significant or medium intensity variation, but is less qualified for realistic ambience with constant intensity compared with the rigidly supported PEHS (RPEHS). Fortunately, the dual-piezoelectric-cantilever energy harvesting system is superior to the RPEHS under all circumstances because the dual-piezoelectric cantilevers are efficiently utilized for electromechanical energy conversion to realize optimal energy harvesting.